DIDACTICAL DESIGN RESEARCH (DDR) PADA HUKUM PASCAL BERDASARKAN KESULITAN BELAJAR SISWA KELAS X MAN CILILIN KABUPATEN BANDUNG BARAT - Adam Hadiana Aminudin; Yudi Dirgantara; Heni Rusnayati (UIN Sunan Gunung Djati Bandung, 2016)
Didactical Design Research (DDR) is a qualitative research with descriptive methods. Aim to make learning design in order to minimize the difficulties of students in Pascal's Law. The population in this research is class X MAN Cililin, while a sampling technique is purposive sampling. The first step for know the student’s learning difficulties in Pascal's Law with knowing Learning Obstacle which this research only focused on epistemology obstacle, so the students of class XI MAN Cililin who had studied Pascal's Law given five numbers essay. From the student’s answers obtained data the student’s learning difficulties in Pascal's Law. From the difficulty of the data, created learning design be adapted with the student’s learning difficulties in Pascal's Law. The design is implemented always improved in every meeting. This is done, and the design can be made better, so that student’s learning difficulties in Pascal's Law can be minimized.